Effect of Ease of Use on User Satisfaction with Zahir Accounting Enterprise Software Among Accounting Students at The University of National Development “Veteran” East Java - Alfindy, Maulina; Sulistyowati, Erna (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the effect of ease of use on user satisfaction with Zahir Accounting Enterprise software among students of the Accounting Study Program at The University of National Development “Veteran” East Java. Methodology: The research method used was a quantitative approach with a sample size of 87 respondents selected through purposive sampling. The data was analyzed using the Partial Least Square (PLS) method with the help of SmartPLS 4.0 software, which enabled effective testing of the relationships between variables. Results: Data analysis shows that ease of use has a significant and positive effect on user satisfaction with Zahir Accounting Enterprise software, with a path coefficient value of 0.587 and a T-statistic of 6.324 > 1.96 (p-value 0.000 < 0.05). The ease of use variable explains 34.4% of the variation in user satisfaction, with the “simplicity” indicator having the greatest influence. Findings: he study reveals that accounting students at UPN “Veteran” East Java tend to feel that the steps to complete tasks in the software are short and simple, which significantly contributes to their level of satisfaction in using the accounting system. Novelty: This study fills a research gap by focusing specifically on the experiences of accounting students as digital natives, who have different characteristics and expectations regarding technology use compared to professional users, offering a new perspective in evaluating accounting information systems in a higher education context. Originality: This research contributes original insights by exploring the relationship between ease of use and user satisfaction in the context of integrated accounting practicum learning, offering new perspectives on the effectiveness of accounting software implementation in an academic environment. Conclusion: Usability was found to have a significant impact on user satisfaction with Zahir Accounting Enterprise software among accounting students. These findings have practical implications for the development of more effective technology-based accounting learning methods and enrich the academic literature on the evaluation of accounting information systems in the context of higher education. Type of Paper: Research article.